Decoding chemical interactions among pomegranate, Aphis punicae, and associated insects in Taif fields through open-loop stripping - M’sakni, Nour Houda; Alsufyani, Taghreed; Alotaibi, Noura J. (Frontiers in Plant Science, 2025)
IntroductionThe escalating threat posed by Aphis punicae to Punica granatum cultivation underscores the urgent need for sustainable, ecologically sound alternatives to chemical pesticides. This study employs a non-targeted analysis of volatile organic compounds (VOCs) emitted by aphid-infested pomegranate (AIP), undergoing multitrophic interactions with natural enemies (Coccinella undecimpunctata) and mutualistic protectors (Tapinoma magnum). These VOCs are hypothesized to function as early biochemical markers of pest stress and semiochemical cues guiding insect behavior, offering potential integration into decision-support tools within integrated pest management (IPM) frameworks. MethodsVOCs were non-destructively collected using open-loop stripping and analyzed via gas chromatography–mass spectrometry under a metabolomics approach. Profiling was conducted across four ecological scenarios through integrated in-situ experimentation: (G1) AIP, (G2) AIP with ants, (G3) AIP with ants and ladybirds (24h), and (G4) AIP with ants and ladybirds (48h). Principal component analysis and heatmap clustering revealed scenario-specific VOC fingerprints. ResultsIn the two-trophic AIP system, early plant stress responses included suppressed emissions of β-farnesene and methyl salicylate, alongside elevated levels of caryophyllene, a compound often associated with herbivore activity. At 24h, under a tritrophic interaction, 4-heptanone, a key ant pheromone, was detected, suggesting a role in interspecies signaling or predator deterrence. After 48h, in the quadripartite trophic interaction, VOCs such as 1-ethyl-3-methylbenzene, 1,3,5-trimethylbenzene, and 1-methyl-1H-imidazole became dominant, likely reflecting aphid-induced signaling affecting multitrophic dynamics. In the same interaction, elevated levels of six herbivore-induced plant volatiles (6-HIPVs), methyl salicylate, β-caryophyllene, sabinene, limonene, pentadecane, and heptadecane, were observed, supporting indirect plant defense by attracting natural enemies. Bioassays showed that C. undecimpunctata exhibited significantly higher attraction to the mixture of 6-HIPVs compared to individual treatments with methyl salicylate or β-caryophyllene. The mixture elicited the highest behavioral response, indicating a synergistic effect among volatiles and supporting their role in enhancing predator attraction. DiscussionTo transition from discovery to application, future research should focus on targeted analysis, compound-specific bioassays, optimized delivery systems, and open-field trials. Assessing these VOCs under varying agroecological conditions, along with evaluating economic feasibility, scalability, and regulatory pathways. This approach will be crucial for translating this chemical ecology framework into effective, climate-resilient IPM strategies tailored to the arid agroecosystems of the Taif and similar environments.